La parola silenzio (ENTHYMEMA, 2019)
My work analyzes the figure of silence and the way it develops in some of Paul Celan’s poems. More in details, it examines the argumentum e silentio, a real inference based on withholding or lacking an answer. In this silence the death of the German language, Celan’s own language, is at stake. It was violated by the Nazis and slaughtered in the crematoriums. The question is how can it be possible to keep on writing poetry in this language and how poetry can still retain the ethical power which would force to avoid that violence, that barbarization. And furthermore, how can that language possibly reclaim itself as his mother tongue. In this regard, Celan proposes an «erschwiegene Wort», a word which is defeated, conquered, torn from the silence of destruction and, at the same time, a silenced word: the word silence. A word said in silence which could lead closer to the remains of that language, so close to reveal its pauses, its articulations, its own uniqueness. Accordingly, we could state that each language is motherly when it finds its rhythm and its measure around something it cannot pronounce. The language takes action. In Celan’s poetry this action is suggested by the word «Spruch» which I suggested to be translated through a linguistic gesture: it is action and its suspension at the same time. This is the only way to demonstrate that the language is at stake and it is motherly. And, in the end, its words are nothing but ‘pure gestures’ - Unworten, as Celan defines them: true witness of something that is there because it is no longer there.
Keywords: Paul Celan; silence; poetry; action; gesture; translation